Qualidade de vida do idoso: comparação entre estratos de alto, rnédio e baixo padrão sócio- econômico - Olinda, Querubina Bringel (1999)
The phenomermm of aging populations has a growing teudency and brings social economícal repercussions with coriseqtiences in the Services and ín the peop.le's welfare. The longevity imposes the need to think ia avoiding the old people suffering and improving their quality of health. Th is descriptive work is aboutthe quality oflife of old age d p copie in the cíty of Fortaleza. It was developed in the period from decernber 1997 to april 1998.The quantitative aim cousísted in mensuring and analysing the data related to variables of gender, age, place of living and origin in high, middle and low social economícal classes: while the subjectiva aspects of quality-of life were shown through a concept presented by the actors ( sample of old people .) and their own performance., resuíting in Health, familiar !ove,{childre.n), peace, religion and other relevam factors. This research was developed through a semi-structured interview and a multídimensional questionar}-' with qualitative and quantitative questions applied to 385 people, not segregated, at the age of sixty and more.Three out of five zones were selected through a probabilistical, stratified and systematic sample,From these zones, six districts were sampled with their respective populations, The quantitative analysís showed among others the following results: There are more women 263 (68,3%) than men 122 (3 1,7%) among old people ín the districts researched. The majority are marriecl - about 200 (51,9%). There are about 134 (34,8%) widowers. From this total 122 (91%) are wornen. The more advanced age group (from 80 to 94 years) are concentrated in the high economícal classes from categories A and B. Concernmg to dwelling , it was noticed that 316 (82,1%) lived in their own houses (paid houses). Al! the rates aualysed suffered great variables with the social classes mainly .in: instruction, general and economícal life conditions. When it was comited in the qualitativo analysís absolute frequencies of variables of values atributed to the concept of quality oflife, the following aspects were great er: health. peace, familiar love and friendship.The old people gave emphasis to familiar love, health, peace, religion and money over factors that promote the quality of life and elected as reductors of the quality of life: Family problems, disease, financial dif^culties, lack of respect and íonelmess. To feel happy was the affirmative response of 336 (87,3%) of the interviewed people. In the testimony of 138 (35,8%) old people, the loireiiness was present. The old people selected as main indicators of evaluation of quality of life the perceived health ,the financial independence, house to live in, the fui 1 affective life and respect. They rated goocl raies of self-evaluation .in general conditions of life 246 (66,1%); anel in the fo llowing aspects: educat iona 1 196 (51,6%); economica l 178 (47,0%) soc io- cultural 20 7 (55,6%); life style 269 (71,2%) and perceived health 261 (68,1%). The rate of old people auionomy who achieved all the group of activities resulted in 219 (56,9%). The old people are not homogeneously distributed. They differ by the social economícal categories whose classes A and B ha ve got greater incomes, better instruetion, better basic sanitatíon, more access to goods and Services, better perveived health and more autonomy, The quality of life expressecl quantitatívely in the best health leveis is associated to categories A and B, and when described quaíitativelv as a value of self-esteem and pleasure of living, it resulted in a rate of general average of 274 (71,7%) of old people. We suggested to the Health Sector to develop indicators that capture readiugs of other realities related to eíderly people and not only concerned to ilIness and death.